Pemanfaatan Teknologi dalam Meningkatkan UMKM Krupuk Stik “Barokah Jaya” Desa Kedungbanteng - Ramadhani, Yunita; Nafiah, Nafiah; Fathoni, Khoirul (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Barokah Jaya Krupuk Stik MSMEs are one of the small and medium businesses that focus on the production and marketing of stick crackers. Despite having quality products, challenges in marketing and distribution often hinder the growth of this business. This study aims to determine the use of technology in improving